2021
DOI: 10.1109/tpds.2020.3028685
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Adoption of Hybrid Encrypted Cloud Data Deduplication With Game Theory

Abstract: Preface unconditional support, and patience. I would like to acknowledge the company of my best friend Dan Wang, who encouraged me when I suffered from frustration and congratulated me sincerely when I attained success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 112 publications
(183 reference statements)
0
8
0
Order By: Relevance
“…In this case, confirming deduplication happened already at the CSP to get an offer of low storage charge becomes essential, our paper aims to solve this issue. For motivating the adoption of our scheme, in another line of our work, we study how to make all related stakeholders to accept and use deduplication schemes by applying game theory to design proper incentive or punishment mechanisms in three cases: client-controlled deduplication [35], [36], server-controlled deduplication [12] and hybrid deduplication [13]. Since our scheme design is built upon the one in [14], belonging to server-controlled deduplication, the incentive mechanism [12] suitable for the server-controlled deduplication schemes can be applied to motivate scheme adoption.…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, confirming deduplication happened already at the CSP to get an offer of low storage charge becomes essential, our paper aims to solve this issue. For motivating the adoption of our scheme, in another line of our work, we study how to make all related stakeholders to accept and use deduplication schemes by applying game theory to design proper incentive or punishment mechanisms in three cases: client-controlled deduplication [35], [36], server-controlled deduplication [12] and hybrid deduplication [13]. Since our scheme design is built upon the one in [14], belonging to server-controlled deduplication, the incentive mechanism [12] suitable for the server-controlled deduplication schemes can be applied to motivate scheme adoption.…”
Section: Further Discussionmentioning
confidence: 99%
“…Another security issue ignored by the previous literature is the correctness guarantee of data duplication check provided by the CSP. Several schemes [12], [13] motivate the CSP to perform deduplication, but ignore that the CSP could cheat the users by providing a fake duplication check result. The reason is simple since the CSP can gain an extra profit by asking the users to pay normal storage fee without granting a deserved discount while performing deduplication to save storage space.…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of redundancy on a local storage can have some benefits, it is not true in the context of cloud computing, where the entire cloud architecture uses different means for a thorough redundancy. Liang et al [10] studied the case of data deduplication in the cloud systems for encrypted data. Their research study investigated the adoption of hybrid encrypted cloud data deduplication (H-DEDU) by means of using the game theory paradigm.…”
Section: Application Of Game Theory In Cryptographymentioning
confidence: 99%
“…Accordingly, he found that game theory allows a higher level of sophistication and efficiency in cryptography as it resolves the issues and security flaws present in conventional cryptographic techniques. Recently, several researchers have shown interest in developing security models and protocols that combine the approaches of cryptography and game theory, as found in [10][11][12][13][14]. These approaches show promising results in terms of performance and security.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that game theory increases the cryptography's efficiency and sophistication by solving some challenges inherent in typical cryptographic methods. Today, there is increasing interest among researchers in innovating security protocols and models that bridge the gap, integrating the practises practically applied in the game theory as well as in cryptography [10][11][12][13][14][15]. These techniques reveal promising outcomes when analysed based on security and performance.…”
Section: Introductionmentioning
confidence: 99%